The Russia-Ukraine war is exacerbating international food price volatility - Rice, Brendan; Hernandez, Manuel A.; Glauber, Joseph W.; Vos, Rob (International Food Policy Research Institute, 2023)
The IFPRI Food Security Portal’s Excessive Food Price Variability Early Warning System is showing excessive levels of price volatility in the four major food commodities: wheat, maize, rice, and soybeans, as well as cotton. Markets for hard and soft wheat and soybeans had already been more volatile than normal since late 2021, well ahead of Russia’s invasion in Ukraine, which began on February 24, 2022. That conflict, coming on top of the ongoing effects of the COVID-19 pandemic, has already contributed to spiking food prices, with possible major consequences for global food security. Rising price volatility poses a distinct threat, as it induces greater market uncertainty, which affects production decisions, and can spur speculative behavior. Both would fan further food price inflation. What is driving the current price volatility, and what are its implications for markets and food security?